Glycodendrimers and Modified ELISAs: Tools to Elucidate Multivalent Interactions of Galectins 1 and 3 - Mark Wolfenden; Jonathan Cousin; Pratima Nangia-Makker; Avraham Raz; Mary Cloninger (Molecules, 2015)
Multivalent protein-carbohydrate interactions that are mediated by sugar-binding proteins, i.e., lectins, have been implicated in a myriad of intercellular recognition processes associated with tumor progression such as galectin-mediated cancer cellular migration/metastatic processes. Here, using a modified ELISA, we show that glycodendrimers bearing mixtures of galactosides, lactosides, and N-acetylgalactosaminosides, galectin-3 ligands, multivalently affect galectin-3 functions. We further demonstrate that lactose functionalized glycodendrimers multivalently bind a different member of the galectin family, i.e., galectin-1. In a modified ELISA, galectin-3 recruitment by glycodendrimers was shown to directly depend on the ratio of low to high affinity ligands on the dendrimers, with lactose-functionalized dendrimers having the highest activity and also binding well to galectin-1. The results depicted here indicate that synthetic multivalent systems and upfront assay formats will improve the understanding of the multivalent function of galectins during multivalent protein carbohydrate recognition/interaction.